Concept of Gap Distance in Motion Interaction between Multiple Floating Bodies - Siow, C.L.; Koto, Jaswar (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2013)
Conceptual study on gap distance between multiple floating structures system was related to the effect of wave particle motion on structure motion. The evaluation on the gap distance between floating structures is an important study for multiple floating structures system especially for deep water liquefied natural gas, LNG exploration because the small gap distance between floating structures is needed to guarantee the effectiveness of LNG transfer. This conceptual study only discussed the effect of wave particle motion to the varying of gap distance between structures based on theoretical point of view. The expected result was generated by simple harmonic motion equation but it is no been validate in this paper. The expected result shown that the wave length and the structures initial gap distance give a significant effect to the minimum gap distance can be achieved by two floating structures. The mentioned minimum gap distance in this paper mean minimum distance between two floating structures achieved due to surge motions induced by wave. In addition, the comparison to various selected case found that at the condition where one structure face wave crest and other structure face wave trough will caused closest minimum gap distance between floating structures but minimum gap distance will be the largest if both structures face wave crest and wave trough at simultaneously. Therefore, proper selection of initial gap distance for different ocean condition can help to avoid crashing happen on structures when experience wave induced motion.